2016
DOI: 10.1111/sjop.12340
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity and discretionary behaviors: Social exchange perspective versus group value model

Abstract: This study examines the relationship between job insecurity and discretionary behaviors, that is, organizational citizenship behaviors (OCB) and counterproductive work behaviors (CWB), with the purpose to extend knowledge on the theoretical explanations for these outcomes. Considering the employment relationship with the organization, two different perspectives are suggested and compared in a multiple mediator model, in order to understand the reasons for discretionary behaviors. We draw upon social exchange t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 54 publications
3
35
0
3
Order By: Relevance
“…Our results provided support for the aforementioned premises, by demonstrating that psychological contract breach plays a mediating role in the relationship between both types of job insecurity and idea generation. This is in line with previous research that has demonstrated that job insecurity is positively related to psychological contract breach (Piccoli & De Witte, 2015;Piccoli, De Witte, & Reisel, 2017;Vander Elst et al, 2016), and that psychological contract breach is negatively related to innovative work behaviour (Ng et al, 2010;Ramamoorthy et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Our results provided support for the aforementioned premises, by demonstrating that psychological contract breach plays a mediating role in the relationship between both types of job insecurity and idea generation. This is in line with previous research that has demonstrated that job insecurity is positively related to psychological contract breach (Piccoli & De Witte, 2015;Piccoli, De Witte, & Reisel, 2017;Vander Elst et al, 2016), and that psychological contract breach is negatively related to innovative work behaviour (Ng et al, 2010;Ramamoorthy et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, job insecure individuals will more likely engage in coping strategies that try to regulate their emotions and distress related to that threat (Lazarus & Folkman, 1984). One way of dealing with such an uncontrollable job situation is to psychologically increase the distance between oneself, and the job and the organisation (psychological withdrawal), in order to reduce the negative impact of a possible job loss (Piccoli, De Witte, & Reisel, 2017). As a result, lower job satisfaction and affective commitment are considered psychological coping reactions frequently associated with job insecurity.…”
Section: Job Insecurity and Performance: Hindrance Effectmentioning
confidence: 99%
“…We administered a survey to employees working in a manufacturing company located in Italy. All participants involved (N = 302) were blue-collar workers, a less studied group in the job insecurity literature compared to other occupational categories (Piccoli et al, 2017). Seventy-eight percent of the respondents were male and 22 percent were female.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The three chosen outcomes have origins in organizational citizenship behavior (OCB), which is a commonly studied outcome in evaluating company policies ( De Gilder et al, 2005 ), especially those related to CSR. As the dimensions of OCB are generally arranged in three categories: favorable attitudes toward organization (e.g., loyalty), favorable behaviors toward organization (e.g., individual initiative), and favorable behaviors toward coworkers (e.g., helping behavior) ( Coyle-Shapiro, 2002 ; Jones, 2010 ), we followed a similar approach in selecting the three outcomes for this study. However, we went further in selecting factors that are beyond OCB-linked variables.…”
Section: Introductionmentioning
confidence: 99%